‘FALSE FRIENDS’ IN POLISH-GERMAN TRANSLATION OF LEGAL TERMINOLOGY - SIEWERT, Katarzyna (Comparative Legilinguistics, 2012)
The term ‘false friends’ refers to lexical units appearing in two languages in identical or similar graphic or phonetic form, but differing in meaning. Such a formal similarity creates a risk of incorrect usage not only by foreign language learners, but also inexperienced translators. The translator’s false friends are particularly dangerous in the translation of legal texts because incorrect translation may sometimes lead to misunderstandings with very serious consequences as a result of distortion of the message in the target language. The present paper aims to show chosen examples of the translator’s false friends which could be terminological traps waiting for inexperienced translators of Polish and German legal texts.